Sex Differences in the Prevalence of and Risk Factors for Abnormal Glucose Regulation in Adults Aged 50 Years or Older With Normal Fasting Plasma Glucose Levels - Zhang, Xinxin; Liu, Jie; Shao, Shuang; Yang, Yuan; Qi, Dongwang; Wang, Conglin; Lin, Qiuxing; Liu, Yue; Tu, Jun; Wang, Jinghua; Ning, Xianjia; Cui, Jingqiu (Frontiers in Endocrinology, 2021)
Aims: Abnormal glucose regulation, which can present as diabetes and prediabetes, has become one of the most common chronic conditions. However, sex differences in the prevalence of and factors associated with abnormal glucose regulation remain unclear. Thus, we aimed to explore sex differences in the prevalence of and factors associated with abnormal glucose regulation in low-income adults in China aged ≥50 years with normal fasting plasma glucose levels. Materials and methods: A total of 2175 individuals aged ≥50 years with normal fasting plasma glucose levels were recruited into this study. After an overnight fast of at least 10 h, individuals underwent an oral glucose tolerance test. Fasting and 2-h plasma glucose levels were measured to determine the state of glucose regulation. Results: Women were more likely than men to have isolated-impaired glucose tolerance (i-IGT) overall (24.7% vs 20.8%; P= 0.034), among individuals aged <65 years (21.7% vs 15.9%; P= 0.012). Among men, independent risk factors for i-IGT were an age of ≥65 years, hypertension, and high serum uric acid (SUA) and triglyceride levels; independent risk factors for diabetes mellitus (DM) were an age of ≥75 years and alcohol consumption. Among women, independent risk factors for i-IGT were central obesity and high levels of high-sensitivity C-reactive protein and SUA; independent risk factors for DM were low education and an elevated white blood cell count. Conclusions: Our findings suggest that conventional cardiovascular disease risk factors (i.e., age, hypertension, and dyslipidemia) associated with high risk of developing DM in men, but poor life style (i.e., obesity) and low education attainment in women. It is necessary for delay or stopping the development of DM among low-income adults in China to implement the personalized scheme of prevention DM between men and women, especially highlight control the risk factors in young and middle aged women.